Vernacular architecture in Portugal: Regional variations - Simões, Rui Nogueira (2019)
This chapter presents the various typologies that can be found in vernacular architecture across Portugal. It will be shown how these variations result from an adaptation to the local contexts, including climatic characteristics. Considerations will also be taken on other aspects of sustainability, including refurbishment, environmental performance, and cultural issues. The chapter consists of the National Survey on Regional Architecture, Regional Variations: Context Considerations, Minho, Trás-os-Montes and Alto Douro, Cova da Beira, Estremadura and Ribatejo, Inland Alentejo, Coastal Alentejo, Lower Alentejo and Algarve, Vernacular revival, Conclusions, and References.